2016
DOI: 10.1007/s00167-016-4015-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyography and plantar pressure during walking in young adults with chronic ankle instability

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
73
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 36 publications
(60 reference statements)
13
73
7
Order By: Relevance
“…142 Koldenhoven et al 143 observed that patients with CAI had greater stride-to-stride variability in the location of their center of pressure during the first 10% of stance phase during walking compared with controls but no differences later in the stance phase, despite their center of pressure staying more lateral. 144 Interestingly, the patients with CAI also exhibited less variability in electromyographic amplitude of the fibularis longus muscle throughout the swing phase and the beginning of the stance phase. 143 During cutting tasks requiring rapid lateral movement, patients with CAI activated the fibularis longus earlier than healthy controls, in a manner similar to that seen while walking.…”
Section: Motor-behavioral Impairmentsmentioning
confidence: 90%
“…142 Koldenhoven et al 143 observed that patients with CAI had greater stride-to-stride variability in the location of their center of pressure during the first 10% of stance phase during walking compared with controls but no differences later in the stance phase, despite their center of pressure staying more lateral. 144 Interestingly, the patients with CAI also exhibited less variability in electromyographic amplitude of the fibularis longus muscle throughout the swing phase and the beginning of the stance phase. 143 During cutting tasks requiring rapid lateral movement, patients with CAI activated the fibularis longus earlier than healthy controls, in a manner similar to that seen while walking.…”
Section: Motor-behavioral Impairmentsmentioning
confidence: 90%
“…increase the risk of recurrent lateral ankle sprains by placing the foot in a more vulnerable position when it is combined with the kinetic gait profiles of patients with CAI who have a laterally deviated center of pressure (COP) of the foot throughout the gait cycle. [9][10][11] Whereas the kinematic gait profiles have been consistent among studies, [2][3][4][5][6][7][8] the muscle-activity gait profiles of patients with CAI have been inconsistent. For example, Hopkins et al 9 observed increased tibialis anterior and peroneus longus activation during stance in patients with CAI.…”
mentioning
confidence: 99%
“…Although fibular spasticity is not well-known clinically, several related studies have been reported in medical literature (Xu et al, 2015;Laddha et al, 2016;Santamato et al, 2019). Louwerens et al (1995) and Koldenhoven et al (2016) reported that hyperactivity of the fibularis muscle-which plays an important role in maintaining balance while walking-causes an imbalance during the stance phase and increases walking speed. Thevenon et al (2013) reported that spasticity of the fibularis longus can cause foot clonus.…”
Section: Introductionmentioning
confidence: 99%